(untitled) (Global Journals of Research in Engineering, 2023)
Diabetes is a serious disease that spreads rapidly around the world and is first surprising Its danger factors are therefore quite high A different technique to identify diabetes at an early stage is to gradually decline in general health This approach will reveal the health of the body s organs before symptoms manifest Using machine learning approaches a framework for the diabetes prediction system is built in this research paper s first stages